Analisis Pengelolaan Limbah Benda Tajam di RS Pratama Tanah Abang Kabupaten Pali Tahun 2026 - Chindy Tri Andini; Arie Wahyudi; Chairil Zaman (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Sharp waste is infectious medical waste that can transmit diseases such as HIV, Hepatitis B, and Hepatitis C through needlestick injuries, making proper management essential to protect healthcare workers and the environment. This study aimed to analyze factors associated with sharp waste management practices at Tanah Abang Primary Hospital, PALI Regency, in 2026. A quantitative cross-sectional design was used involving all healthcare workers engaged in waste management, with 94 respondents selected through total sampling. Data were collected using questionnaires and direct observation, then analyzed through univariate, bivariate Chi-Square, and multivariate backward stepwise logistic regression analyses. Bivariate results showed significant associations between sharp waste management and knowledge (p=0.001; OR=5.273), attitude (p=0.001; OR=5.935), safety box availability (p=0.013; OR=2.903), and management supervision (p=0.009; OR=3.154). Age, gender, education, and hospital policy were not significantly associated. Multivariate analysis identified staff attitude and knowledge as the dominant predictors. The study concludes that sharp waste management is mainly influenced by internal awareness, requiring stronger educational supervision and behavior-based safety culture to sustain staff compliance.